Exploring self-esteem and personality traits as predictors of mental wellbeing among Chinese university students: the mediating and moderating role of resilience - Cui, Zhenti; Lin, Zihan; Ren, Jingjie; Cao, Yingdong; Tian, Xiaofei (Frontiers in Psychology, 2024)
Introduction The mental health of university students is influenced by a variety of factors, including self-esteem and personality traits, with resilience playing a crucial role in mediating and moderating these relationships. This study investigates the intricate dynamics affecting mental well-being in Chinese university students, focusing on the roles of self-esteem, personality traits, and the interventional effects of resilience. Methods A cross-sectional survey was conducted with 689 students, aged on average 20.3 years, between April and July 2022. The Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS) was used to assess mental well-being, while resilience, personality traits, and self-esteem were evaluated using the revised Connor-Davidson Resilience Scale (CD-RISC), the Chinese version of the Big Five Inventory-2 (BFI-2), and the Texas Social Behavior Inventory (TSBI), respectively. Results Analysis revealed significant correlations between self-esteem, personality traits, and both resilience and mental well-being. Resilience was found to partially mediate the relationship between self-esteem and mental well-being and fully mediate certain aspects of the relationship between personality traits and mental well-being. Additionally, tenacity and autonomy were identified as moderators in the link between specific personality traits and mental well-being. Discussion The findings highlight the complex interplay between self-esteem, personality traits, resilience, and mental well-being, underscoring the critical role of resilience. This insight is pivotal for developing targeted interventions to bolster mental well-being among university students, emphasizing the need for multifaceted support strategies to enhance student mental health.